Patient experience with eosinophilic esophagitis symptoms and impacts on daily life based on in-trial qualitative interviews - Calvin N. Ho; Harald Fjällbrant; Evan S. Dellon; Cecilio Santander; Marc E. Rothenberg; Julie Bailey; Shehan McFadden; Jason Ritchie (Journal of Patient-Reported Outcomes)
Abstract Purpose Eosinophilic esophagitis (EoE), a chronic immune-mediated progressive disease, causes dysphagia, food impaction, abdominal pain, vomiting, and heartburn. EoE requires long-term monitoring and can affect quality of life owing to its symptoms and associated emotional and social burden. This study aimed to understand patients’ experiences with EoE. Methods Semi-structured longitudinal interviews were conducted with patients from MESSINA, a phase 3 placebo-controlled trial evaluating benralizumab for EoE. Interviews were held at two different times to assess the impact of EoE on patients’ lives before and during trial participation. Data were analyzed qualitatively to develop detailed patient profiles. Results The MESSINA trial was terminated prematurely. Of the 34 patients recruited for the first interview, 15 (44%) completed the second interview and 11 patient profiles were developed. Patients were a demographically diverse group with varying experiences. The primary reported symptom was difficulty swallowing (n = 11), leading to serious consequences like choking and hospitalization (n = 2). Other symptoms included pain when swallowing (n = 7), reflux (n = 6), and stomachache (n = 6). In the second interview, most (n = 9) patients reported moderate improvements in symptoms, while others experienced symptom recurrence or worsening. EoE had a significant negative impact on social and emotional well-being, and professional lives. Trial participation improved emotional well-being for some; however, concerns about the need for ongoing treatment were noted. Conclusion This study highlighted emotional and social burdens of EoE. The encouraging feedback on study participation underscores the importance of patient insights in developing holistic management strategies for EoE.